2000
DOI: 10.1002/(sici)1097-0142(20000515)88:10<2298::aid-cncr14>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal color Doppler ultrasonic characterization of benign and malignant ovarian cystic teratomas and comparison with serum squamous cell carcinoma antigen

Abstract: BACKGROUND The preoperative diagnosis of squamous cell carcinoma (SCC) arising in mature cystic teratoma of the ovary remains difficult. The purpose of this study is to examine the usefulness of transvaginal color Doppler ultrasound (TV‐CDU) in differentiating malignant (SCC) from benign cystic teratoma of the ovary. METHODS Eighty‐eight patients with an ovarian tumor showing gray scale sonographic appearances of mature cystic teratoma were preoperatively evaluated for the presence or absence of intratumoral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 28 publications
2
32
0
6
Order By: Relevance
“…from Japan has differentiated malignant transformation from benign cystic teratomas of the ovary by evaluating the presence or absence of intratumoral blood flow along with blood flow resistance in tumor vessels by using transvaginal color Doppler ultrasound. 10 We advocate the use of the combined diagnostic modality to increase the sensitivity and specificity of the malignant transformation of the teratoma.…”
Section: Commentmentioning
confidence: 99%
“…from Japan has differentiated malignant transformation from benign cystic teratomas of the ovary by evaluating the presence or absence of intratumoral blood flow along with blood flow resistance in tumor vessels by using transvaginal color Doppler ultrasound. 10 We advocate the use of the combined diagnostic modality to increase the sensitivity and specificity of the malignant transformation of the teratoma.…”
Section: Commentmentioning
confidence: 99%
“…3,8,9 Malign dönüşümü belirlemede tümör belirteçlerinden de yararlanılabilmektedir. Yükselmiş CA125 ve CA19-9 malign dönüşümde uyarıcı olmalıdır.…”
Section: Discussionunclassified
“…Ayrıca skuamöz hücreli karsinom diferansiasyonu varlığında, serum skuamöz hücreli kanser antijeninin, malign dönüşümü belirlemede yararlı olabileceği bildirilmektedir. 9 FIGO Evre IA olarak değerlendirilen olguda, batın yıkama sıvısı ve TAH, bilateral SO tedavisi yeterli bulundu. İntraoperatif frozen kesit incelemesinde malign tanısı alan ya da daha ileri evre olduğu düşünülen tüm hastalarda tam cerrahi evreleme yapılmalı, klinikopatolojik prognostik faktörler eşliğinde hastalar adjuvan tedavi ve izlem açısından değerlendirilmelidir.…”
Section: Discussionunclassified
“…These results suggested that, so far, a CT or MRI is helpful only when characteristic images such as transmural invasion or the spread of malignant tumors become apparent (15). Another report suggested that evaluating the presence or absence of intratumoral blood flow, together with blood flow resistance in tumor vessels using transvaginal color Doppler ultrasound may be more useful in differentiating malignant (SCC) from benign cystic teratomas of the ovary than by measuring serum SCC levels (16).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%